Building And Evaluating Digital Elevation Models (Dem) Byusing Geographic Information System - Eyed, Safea; Kadora, Aisha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed for using Geographic Information System (GIS) in producing Digital Elevation Model (DEM) for Dimas District, By applying various methods: Spatial Analyst, Geo Statistical Analyst, Triangulated Irregular Network (TIN), and interpolating DEM from contour lines. The study showed that the best methods for interpolating DEM is Kriging method, Which interpolated an evaluated surface for scattered points which had (Z values) whether they were closed or scattered from each other. And (TIN) method which required less area on hard disc to be stored comparing with other methods, and it’s perfect for representing surfaces in wide areas, Also generating DEM from contour lines produced DEM which had very accurate representing for surfaces.